2008
DOI: 10.1007/s00595-007-3721-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of secondary tricuspid regurgitation after left-sided valve replacement

Abstract: An aggressive repair of accompanying TR should be performed at the time of initial surgery in patients with a huge left atrium, atrial fibrillation, long time from onset to surgery, or tricuspid rheumatic changes. DeVega's tricuspid annuloplasty therefore helps prevent a progression of TR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 17 publications
6
38
1
1
Order By: Relevance
“…The predictive role of left atrium size in FTR progression following MVR was well described by previous retrospective studies (13,28,29). In our study, the left atrium diameter was found to be significantly different both preoperative and postoperatively between groups.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The predictive role of left atrium size in FTR progression following MVR was well described by previous retrospective studies (13,28,29). In our study, the left atrium diameter was found to be significantly different both preoperative and postoperatively between groups.…”
Section: Discussionsupporting
confidence: 79%
“…Preoperative ejection fraction was not shown as a risk factor for FTR but almost all studies as well as ours also investigated patients with normal or mildly decreased ejection fraction (1,13,28,29). Therefore, we believe that more studies are required to evaluate patients with moderate or severe left ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 73%
“…Thirty-six studies were potentially eligible and after being full-text screened, 11 publications [17,18,19,20,21,22,23,24,25,26,27] were eligible for our meta-analysis. The characteristics of these 11 studies are listed in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we found a strong association of rheumatic etiology with residual TR (OR 3.22, 95% CI 2.19-4.75). The time from onset to surgery was reported to be an independent risk factor for late TR in only 1 Chinese study [21]. A long disease course and iterative left-sided valve diseases that have not been corrected in time can lead to increased left atrial size and pressure, secondary pulmonary hypertension and consequent RV remodeling and dysfunction, eventually leading to progression of late TR.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in our data the E/E' ratio, which reflects LA factors in late TR after left-side cardiac surgery. 22- 25 Kim et al found that AF predisposed patients undergoing mitral valve surgery to late TR progression, which could be prevented by the maze operation. 26 In addition, they showed that the absence of RA mechanical activity was a predictor for progression of late TR in a subgroup analysis of 38 patients who had 1/128 vs. 2/83; P=0.563).…”
Section: Beneficial Effect Of La Activity On Long-term Outcomesmentioning
confidence: 99%